The Utility of Endoscopic Biopsies in Patients with Normal Upper Endoscopy. (10th July 2016) - Teriaky, Anouar; AlNasser, Abdullah; McLean, Carolyn; Gregor, James; Yan, Brian
Abstract : Background and Aims . Upper endoscopy is a valuable tool in the workup of gastrointestinal (GI) complaints. The purpose of this study is to determine cost and yield of taking biopsies in a normal upper GI tract. Methods . This is a retrospective study where all upper GI biopsies were identified between May 2012 and April 2013, at a tertiary care center. Clinical, procedural, and pathology reports were reviewed to identify patient demographics, procedure information, and pathology diagnosis. Results . Biopsies of the upper GI tract were taken in 1297 patients with normal upper endoscopies. In patients with normal upper endoscopy, 22% of esophageal, 44% of gastric, and 12% of duodenal biopsies were abnormal. The most frequent abnormality was reflux esophagitis in 16% of esophageal biopsies, chronic gastritis in 23% of gastric biopsies, and increased intraepithelial lymphocytes in 6% of duodenal biopsies. The additional cost for taking biopsies in a normal upper GI tract for a diagnosis of eosinophilic esophagitis was $2963 Canadian (CAD), H. pylori associated gastritis was $1404 CAD, and celiac disease was $3024 CAD. Conclusions . The yield of biopsy in normal upper endoscopy varied with location, but the additional expense can be costly and should be tailored to appropriate clinical situations.